2015
DOI: 10.5430/afr.v4n3p55
|View full text |Cite
|
Sign up to set email alerts
|

Book-Tax Income Differences and Major Determining Factors

Abstract: Book-tax income differences frequently serve as a key proxy in studies investigating earnings management and tax sheltering activities. This is reasonable because managers can manage either book income or tax income to accomplish their personal agendas. However, because a substantial portion of the book-tax differences are affected by unidentified factors, researchers should use them with caution and include additional relevant variables that could augment their findings. JEL classification: M4, K34, L25

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…On the other hand, the temporary differences that cause a future tax liability create a deferred tax liability. The two main accounts that contribute to these differences are depreciable tangible assets and intangible assets (Lee et al, 2015). Deferred tax liabilities are recognized when tax expense is greater than the tax payable.…”
Section: Deferred Tax and Earnings Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the temporary differences that cause a future tax liability create a deferred tax liability. The two main accounts that contribute to these differences are depreciable tangible assets and intangible assets (Lee et al, 2015). Deferred tax liabilities are recognized when tax expense is greater than the tax payable.…”
Section: Deferred Tax and Earnings Managementmentioning
confidence: 99%
“…Some managers misuse the flexibility provided by accounting standards to manipulate tax for accomplishing their personal earnings objectives which might affect the country welfare (Lee, Vetter, Williams, & Research, 2015;Mulyadi, Anwar, & Sciences, 2015). The accounting scandals like Enron, WorldCom showed that managers are able to manipulate earnings in the way they plan.…”
Section: Introductionmentioning
confidence: 99%
“…BTD is primarily attributed to two factors: (1) different income calculation procedures for book and tax revenue as well as (2) different strategies employed by management to boost book income while reducing tax revenue. BTD can therefore originate from earnings management, tax avoidance, or both (Lee, Vetter, & Williams, 2015). Hidayati and Fidiana (2017) explain that one item of the company's corporate social responsibility (CSR) involves costs that can be deducted as business expenses, such as community health initiatives, scholarship programs, and environmental protection, which can be associated with tax avoidance activities.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon causes tax avoidance that possibly committed by tax payer for their tax planning. Besides, this book tax differences is often used as factor in research due to it's usability to track profit management and tax activity closely related with tax avoidance (Lee, Vetter, & Williams, 2015).…”
Section: Introductionmentioning
confidence: 99%